Effective scheduling mechanism for a mixture of 5G multimedia use cases - Mohd Ramli, Huda Adibah; Hassan Abdalla Hashim, Aisha; Asnawi, Ani Liza (Elsevier, 2023)
This paper proposes a novel mechanism to address the challenging scheduling problem which is to maximize the ultra-Reliable Low Latency Communication (uRLLC) and enhanced Mobile Broad Band (eMBB) capacity at the desired Quality of Service (QoS) in the downlink Fifth Generation (5G) network. Though some packet scheduling mechanisms that can maximize the network capacity at the desired QoS are available, they were developed for before 5G mobile communication networks. These mechanisms may not perform well in the unique 5G framework that holds distinct characteristics. Conversely, the available 5G packet scheduling mechanisms were mostly developed to maximize capacity when the network contains only one 5G multimedia use case, assumed an ideal simulation environment in the performance evaluation, considered the legacy fixed numerology of 1 ms slot length and make use of mathematical analysis to maximize the desired metrics. Extensive performance evaluations conducted via computer simulations suggest the effectiveness of the proposed mechanism. At the desired uRLLC QoS which is Packet Error Rate (PER) at 10-5 threshold, the proposed mechanism maximizes the network capacity by 52.5% over a benchmark mechanism known as Virtual Token Modified-Largest Weighted Delay First (VTM) when an equal distribution of uRLLC and eMBB users are available.